HISTORICAL ROOTS OF THE MARTIANO EDUCATIONAL PROJECT - Pérez Cruz, Felipe de Jesús (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
I am interested in the study of the Cuban, Caribbean and Latin-American pedagogical thought. Since the theoretic and methodological point of view, it favors the study of the socio cultural fabric and the mentalities, from the axis of the ideologies and the political ideas especially. I divide of thinking that the movements of ideas, projects and pedagogic actions that from the last decade of the 18th century developed in Cuba, turn out to be vital for the boarding of the History of the Education in the country, and precisely Jose Martí inherits and develops this pedagogic tradition, with the offer of an educational cultural revolutionary project that I impress the theory and the pedagogic practice of his epoch, and it comes out to the present day. I assume the criterion relative to the existence in Jose Martí of a pedagogy and didactics organic. To prove the historicity and systemic unit of this budget turns out to be the principal task that I have planned.